CRUCIAL COMPONENTS: EXPLORING HOW REVIEW FORMATS AFFECT PURCHASES - Wang, Xiao Jun; Liu, Yuan; Zhou, Jing Hua (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
The escalating trend of online shopping has propelled the significance of online reviews as a potent influencer of consumer behavior. With a focus on the Chinese market, where online shopping has surged dramatically, this study examines the impact of online reviews on consumers' purchasing decisions. The proliferation of online shoppers, exemplified by 749 million individuals in China as of June 2020, underscores the pervasive influence of digital commerce. Notably, the pivotal role of online reviews is evident, with 77.5% of consumers engaging with these reviews, as reported by the China Internet Network Information Center (CNNIC). Moreover, empirical evidence from a survey of 140 consumers underscores that 91.43% of purchase determinations are contingent on both the volume and sentiment of reviews. A distinctive observation pertains to the diverse presentation of online reviews on various e-commerce platforms. This study sheds light on this phenomenon, illustrating that platforms like Taobao.com and Tmall.com employ a frequency format (e.g., positive reviews: 1,672; total reviews: 1,823), while JD.com and Vip.com utilize a percentage format (e.g., positive review ratio: 91.7%; total reviews: 1,823). Through this investigation, the study unveils the intricate interplay between review presentation formats and consumers' decision-making processes in the context of online shopping.